2015
DOI: 10.3389/fpsyg.2015.00121
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of attendance at fitness center: a comparison between the theory of planned behavior, the social cognitive theory, and the physical activity maintenance theory

Abstract: In the processes of physical activity (PA) maintenance specific predictors are effective, which differ from other stages of PA development. Recently, Physical Activity Maintenance Theory (PAMT) was specifically developed for prediction of PA maintenance. The aim of the present study was to evaluate the predictability of the future behavior by the PAMT and compare it with the Theory of Planned Behavior (TPB) and Social Cognitive Theory (SCT). Participation rate in a fitness center was observed for 101 college s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 63 publications
4
31
0
Order By: Relevance
“…Based on our findings, a more subtle segmenting of OE, which exceeds the dimensions of proximal and distal OE, and possibly also a detachment of expectancy (including expected likelihood of occurrence) and value could be addressed in future studies. Similarly, recent work in the physical activity domain suggested focusing on affective determinants of behavior (Rhodes et al, 2009 ; Jekauc et al, 2015 ) and systematizing different dimensions of OE (French et al, 2005 ; Conner et al, 2011 ; Gellert et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, a more subtle segmenting of OE, which exceeds the dimensions of proximal and distal OE, and possibly also a detachment of expectancy (including expected likelihood of occurrence) and value could be addressed in future studies. Similarly, recent work in the physical activity domain suggested focusing on affective determinants of behavior (Rhodes et al, 2009 ; Jekauc et al, 2015 ) and systematizing different dimensions of OE (French et al, 2005 ; Conner et al, 2011 ; Gellert et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though there is limited research in this area, there is some evidence that psychological stress negatively predicts physical activity maintenance. Individuals with more life stress are more likely to be irregular exercisers (Jekauc et al, 2015), and those that are starting exercise programs have more difficulty maintaining exercise when they are experiencing stress, whereas individuals who are long-time exercisers may respond to stress with greater exercise participation (Clark et al, 2011, Lutz et al, 2010). Increased stress and decreased life satisfaction may overwhelm coping resources reducing self-regulation capacity and consequently leading to early termination (e.g., Fields et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that individuals with higher body mass index (BMI), who are previously physically inactive, and are motivated to lose weight rather than to improve health are more likely to terminate their memberships (Sperandei et al, 2016). Other research has shown that social cognitive predictors (i.e., self-efficacy, outcome expectancies, barriers, and facilitators) are significant predictors of fitness center visits (Jekauc et al, 2015). To our knowledge, there have not been any additional peer-reviewed studies examining this important area.…”
Section: Introductionmentioning
confidence: 99%
“…For health-enhancing effects, it is recommended that adults engage in at least 150 minutes moderate-to-vigorous (MVPA) a week [8]. However, looking at PA levels in several countries [9,10], the question how to improve PA adherence is a critical one [11,12]. In this context, PA enjoyment has been shown to be an important factor theoretically and empirically [13].…”
Section: Introductionmentioning
confidence: 99%